A polymorphic GGC repeat in the NPAS2 gene and its association with melanoma. Issue 15 (September 2017) - Franzoni, Alessandra; Markova-Car, Elitza; Dević-Pavlić, Sanja; Jurišić, Davor; Puppin, Cinzia; Mio, Catia; De Luca, Marila; Petruz, Giulia; Damante, Giuseppe; Pavelić, Sandra Kraljević
Circadian clock regulation in mammals is controlled by feedback loops of a set of circadian genes. One of these circadian genes, NPAS2, encodes for a member of the bHLH-PAS class of transcription factors and is expressed in the forebrain and in some peripheral organs such as liver and skin. Other biological processes are also regulated by circadian genes. For example, NPAS2 is involved in cell proliferation, DNA damage repair and malignant transformation. Aberrant expression of clock genes has been previously observed in melanoma which led to our effort to sequence the NPAS2 promoter region in this cancer type. The NPAS2 putative promoter and 5′ untranslated region of ninety-three melanoma patients and ninety-six control subjects were sequenced and several variants were identified. Among these is a novel microsatellite comprising a GGC repeat with different alleles ranging from 7 to 13 repeats located in the 5′ untranslated exon. Homozygosity of an allele with nine repeats (9/9) was more prevalent in melanoma than in control subjects (22.6% and 13.5%, respectively, P : 0.0206) suggesting that some NPAS2 variants might contribute to melanoma susceptibility. Impact statement: This report describes a variable microsatellite repeat sequence located in the 5′ untranslated exon of NSPAS2, a gene encoding a clock transcription factor. Significantly, this study is the first to show that a variant copy number GGC repeat sequence in the NPAS2 clock gene associates with melanoma risk and which may be useful in the assessment of melanoma predisposition.